City and Countryside Revisited. Comparative rent movements in London and the South-East, 1580-1914 - David Ormrod; James M. Gibson; Owen Lyne (University of Kent, School of Economics, 2011)
Economic historians have traditionally argued that urban growth in England was driven primarily by prior improvements in agricultural supply in the two centuries before the industrial revolution. Recent revisionist scholarship by writers such as Jan Luiten van Zanden and Robert Allen has suggested that 'the city drove the countryside, not the reverse'. This paper assembles new serial data on urban and agricultural rent movements in Kent, Essex and London, from 1580-1914, which enables us to provide a tentative estimate of the strength of the urban variable and the productivity of land across the rural-urban continuum. Our initial findings support the revisionist view, and throw new light on London's position within the wider metropolitan region. Comparative rent movements suggests a greater continuity between town and countryside than has often been assumed, with sharp increases in rental values occurring on the rural-urban fringes of London and the lower Medway valley.
Keywords: N53; N93; Q15; R12; R14; Y1; 330; Europe; pre-1913; agriculture; land-use; tenure; rural-urban relations; spatial competition; urban history